A fully implicit finite difference scheme for velocity and temperature coupled solutions of polymer melt flow - Vaz Jr. M.* (2007)
This work presents a fully implicit finite difference scheme aimed at simulation of polymer melt flow in channels and mould cavities. This class of problems is characterized by strong material non-linearity and coupling of momentum, heat and mass transfer. The computational approach is based on the generalized Newtonian model and utilizes central discretization for both diffusive and convective terms, collocated meshes and artificial dissipation control to handle spurious pressure modes. The formulation accounts for the full interaction between the thermal effects caused by viscous heating and the momentum diffusion effects dictated by a shear rate and temperature-dependent constitutive model. Solutions for plane channels and asymmetric sudden expansion illustrate application to polymer melt flow. Copyright © 2006 John Wiley & Sons, Ltd.